Unpacking the Learning Ecosystems Framework: Lessons from the Adaptive Management of Biological Ecosystems - Hecht, Marijke; Crowley, Kevin (Journal of the Learning Sciences, 2020)
An ecological framework is often used to describe the context for learning in educational research and practice. However, there is often a focus on descriptive aspects that frame the ecosystem as a complicated set of interconnected elements—but not a true complex problem. Acknowledging connections between ecosystem elements is not enough to affect the systemic change that the wicked problem of education requires. In this paper, we argue for moving toward a more robust framework that takes seriously the notion of learning happening via relational processes between system elements, and looks more deeply at the ways in which those dynamic elements are interacting in complex, multiscalar ways. We promote drawing more heavily from ecologists’ understanding of biological systems, particularly the application of concepts drawn from adaptive management strategies used in the field of restoration ecology. We present an argument to decentre our field’s typical focus on individual youth, just as ecologists have moved biology away from an emphasis on individual organisms. We postulate that decentring youth enables new ways of thinking about learning ecosystem design and management. We then explore three specific concepts used in adaptive management in ecology: ecotones, keystone and indicator species, and disturbance and resilience.